The expression, purification & characterization of a recombinant cellulase from cryptococcus gattii - Moodley, Dylan (My University, 2022)
Cryptococcus gattii (Sanfelice) Vuillemin is an opportunistic pathogen and a primary aetiological agent of cryptococcosis. There are approximately 1 000 000 new cases of cryptococcosis reported per annum, resulting in nearly 625 000 deaths. Cryptococcus gattii has been isolated from a number of different environmental sources such as avian guano, soil and most commonly woody debris which is rich in cellulose. An open reading frame within the genome of C. gattii (WM276) has been annotated as a putative cellulase, however the structure and function of this gene-product remain unresolved. This is particularly glaring given that infection by this yeast is linked to environmental sources. As such, the overall aim of this project was to recombinantly overexpress, purify, and characterize the putative cryptococcal cellulase in terms of its structure and function. The construction of an automated homology model revealed that despite the presence of the MBP-tag, the cellulase adopted a typical (α/β)8 TIM barrel fold, which is indicative of the glycosyl hydrolase family 5 (GH5). The fusion enzyme, MBP-cellulase, was successfully overexpressed in Escherichia coli as a soluble protein and affinity purified to homogeneity using amylose affinity chromatography. Investigation of the structural character of the enzyme revealed that MBP-cellulase has a secondary structure composed primarily of α-helices with the presence of some β-sheets. Tertiary structure analysis highlighted that MBP-cellulase undergoes a conformational change in order to accommodate its ligand, sodium carboxymethyl cellulose, suggesting that the MBP does not block the active site. Quaternary structure analysis revealed that MBP-cellulase exists as a 90 kDa monomer. Finally, insights into MBP-cellulase’s functionality delineated the fusion enzyme’s optimal cellulolytic parameters, which were a pH of 6, a temperature of 50 ˚C and the presence of 500 mM sodium chloride. The presence of divalent metal ions had a negligible to deleterious effect on MBP-cellulase’s cellulolytic ability, which potentially rules out the enzyme’s requirement for a metallic co-factor. To the best of our knowledge, this work represents the first overexpression, purification, and characterization of a cellulase from C. gattii WM276. Moreover, this is the first illustration of the structural character of a cellulase from any cryptococcal pathogen. The thermotolerant and halotolerant nature of this particular cellulase, makes it useful for industrial applications, and adds to our understanding of the pathogen’s environmental physiology.A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2022
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2022